The Role of the School Library in Improving Students' Literacy - Ahmad Rizaldi; Fadhilatul Hamdani (Librarianship in Muslim Societies, 2023)
This study discusses the literacy activities of students at school, which aims to determine the literacy activities carried out and the library's role in increasing the literacy of SDI Al-Azhar 4 students. In addition, to find out the obstacles and solutions they face. The research method used for this study is a qualitative approach and this type of case study research. Data collection techniques in this study were interviews, observation, and literature review. The results of this study include 1). Although SDI Al-Azhar 4 has not implemented the School Literacy Movement (GLS) in the school curriculum, it has indirectly implemented GLS in their schools through reading activities in class, storytelling, book reviews, and library classes. 2) The library has a role as a facilitator in increasing the literacy of SDI Al-Azhar 4 students by facilitating reading materials, library class hours, and library activities. In addition, the library (librarian) also plays the role of educator in literacy activities through storytelling, watching films, and reading in classes organized by the library. 3). Obstacles libraries face in providing literacy activities, namely reading materials that are easily damaged because they are often read by students, which are then resolved with a solution given a budget for repairs and procurement of new books. Besides that, another obstacle faced is the Covid-19 pandemic which has changed the learning system by not being face-to-face. This problem is given a solution by carrying out literacy activities online.